(untitled) (Bangladesh Journal of Dental Research & Education, 2015)
Tooth brushing is such a familiar process that it is easy to forget how crucial it is to oral health and how important it is to brush properly. Twenty three patients were selected in the age-group of 30-40 having tooth brushing abrasion in the cervical region of at least three teeth and taught the Modified Stillmans Brushing Technique during a four week pre-test period. Plaque disclosing agent was used prior to and after brushing to educate the subjects .At the end of the pre-test period a complete oral prophylaxis was done to obtain a zero plaque score. The patient was asked to refrain from any oral hygiene procedure for next 48 hours and nonfibrous regular diet was advised. After 48 hours pre-brushing plaque scoring was recorded according to Turesky-Gilmore-Glickman Modification of the Quigley-Hein plaque index. A split mouth design was followed to record the post brushing plaque scores. Each time the patients were asked to brush on both upper and lower quadrants of one side for recording post-brushing plaque scores without dentifrice first and then brush on the upper and lower quadrants of the other side for recording plaque scores with dentifrice. The three treatment groups viz. Pre-brushing, Post-brushing without dentifrice and Post-brushing with dentifrice when subjected to ANOVA confirmed that the Modified Stillmans Technique effectively removes plaque in both post-brushing situations (p<0.01).The subjects showed a reduction in plaque levels in the Post-brushing trials as indicated by C.D. value (0.0179) (p<0.05). It can be derived from the statistical analysis that if properly done tooth brushing removes plaque effectively when used with or without dentifrice. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22451 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 06-10